Elucidating the pH-dependent conformational transitions of eryngin: Insights from molecular dynamics simulations - Gourav Choudhir; Mohammad Shahid; Asimul Islam (Informatics in Medicine Unlocked, 2024)
Eryngin is a novel antifungal peptide derived from the Pleurotus eryngii mushroom with potential drugproperties. This study aims to explore the stability and structural integrity of eryngin at different pH levels found within the human body. The molecular dynamic simulation method showed that eryngin maintains its overall structure within pH ranging from 1.5 to 8. The free energy landscape analysis showed that the free energy was distributed in the range of 12.80–19.30 kJ/mol. This investigation suggests that eryngin could potentially function effectively as a treatment for various diseases at different body sites with varying pH environments, owing to its ability to retain its secondary structure. Additional research is necessary to fully comprehend the biological activity of eryngin and its potential as a therapeutic agent.